Penguatan Ekonomi melalui Produksi APE Kreasi Tiga Tepung dengan Flour Press Cutter dan Optimalisasi Digital Marketing di Desa Karangtanjung, Kecamatan Candi Kabupaten Sidoarjo - Listyowati, Anies; Rosidah, Cholifah Tur; Kurniawan, Widiar Onny; Sembodho, Ageng; Febrianti, Triana (Universitas Pahlawan Tuanku Tambusai, 2026)
Early Childhood Education (ECE) is a crucial foundation in preparing Indonesia’s Golden Generation 2045. However, limited learning media remains a challenge, including for Ananda Toys MSME in Karangtanjung Village, Sidoarjo, which produces Educational Play Tools (EPT). The main problems include the absence of business legality, limited product innovation, simple marketing practices, and weak financial record-keeping. This community service program aims to empower MSMEs through assistance in obtaining business legality, training in innovative EPT production based on the Flour Press Cutter, strengthening product branding and digital marketing, and training in simple financial recording. The program was implemented using a participatory approach through socialization, training, mentoring, and evaluation, involving 40 participants consisting of business actors, youth organizations (Karang Taruna), PKK members, and PAUD/elementary school teachers. The results show an increase in MSME competitiveness through the acquisition of business legality, product innovation, expanded digital marketing, and more systematic financial management, while also supporting improvements in the quality of early childhood education and community welfare.